2016
DOI: 10.3897/zookeys.577.6149
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm feeding: Microbial colonization of food promotes the growth of a detritivorous arthropod

Abstract: Feeding on plant material is common among animals, but how different animals overcome the dietary deficiencies imposed by this feeding strategy is not well understood. Microorganisms are generally considered to play a vital role in the nutritional ecology of plant feeding animals. Commonly microbes living inside animal bodies are considered more important, but recent studies suggest external microbes significantly shape plant-feeding strategies in invertebrates. Here we investigate how external microbes that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…The latter excludes different host genotypes as the primary driver of microbiome composition in this species and makes a shift due to environmentally acquired bacteria all the more likely. The effect of different food sources on the gut microbiome has been more formally tested in P. scaber , confirming that different food sources shape taxonomic composition of the gut microbiome at the phylum level ( Horvathova et al, 2016 ).…”
Section: The Big Picture: the Terrestrial Isopod Microbiomementioning
confidence: 84%
See 1 more Smart Citation
“…The latter excludes different host genotypes as the primary driver of microbiome composition in this species and makes a shift due to environmentally acquired bacteria all the more likely. The effect of different food sources on the gut microbiome has been more formally tested in P. scaber , confirming that different food sources shape taxonomic composition of the gut microbiome at the phylum level ( Horvathova et al, 2016 ).…”
Section: The Big Picture: the Terrestrial Isopod Microbiomementioning
confidence: 84%
“…Another recently published investigation of the hindgut microbiome in P. scaber using Illumina sequencing ( Horvathova et al, 2016 ) enables us for the first time to compare the gut microbiomes of two isopod species: while the gut microbiome of P. scaber was similar to that of A. vulgare in terms of bacterial diversity at the phylum level (20 phyla), microbiome composition was quite different: Proteobacteria represented by far the most abundant phylum in both species (approximately 85%) but Alphaproteobacteria were more abundant than Gammaproteobacteria in A. vulgare , whereas the opposite was the case in P. scaber . Similarly, the Mollicutes Hepatoplasma and Bacilloplasma accounted for 8.5% of the gut microbiome in A. vulgare , while they were negligible in P. scaber (0.72%).…”
Section: The Big Picture: the Terrestrial Isopod Microbiomementioning
confidence: 99%
“…Our study showed that gut bacteria from several invertebrate species were dominated by phylum Proteobacteria, Bacteroidetes, and Firmicutes. Proteobacteria is the most representative phylum among all insects studied so far (Jones et al, 2013;Yun et al, 2014;Horváthová et al, 2016).…”
Section: Identification Of Sequenced 16s Rdna Fragments From Dggementioning
confidence: 99%
“…For organisms feeding on plant materials, the proportion of non-C elements in their food may be more limiting than energy (Pokarzhevskii et al, 2003;Moe et al, 2005) and diet supplementation with high-quality resources may promote the development of animals feeding on dead plant matter Weiner, 2014, 2016;Filipiak et al, 2016;Horvathova et al, 2016). Hence, it might be advantageous to include in the diet plant matter that is nutritive, easily available in considerable mass and relatively easily digestible, i.e., pollen.…”
Section: Introductionmentioning
confidence: 99%